A mortality study on male subjects exposed to polyfluoroalkyl acids with high internal dose of perfluorooctanoic acid - Girardi, Paolo; Merler, Enzo (Environmental research, 2019)
The aim of the present study was to examine the association between exposure to polyfluoroalkyl substances (PFASs) and mortality (1970–2018) in a cohort of 462 male employees who had worked at least six months before 2009 for a factory (14,658 person-years; 107 deaths, average follow-up time 31.7 years), which had been producing perfluorooctanoic acid (PFOA), perfluorooctanesulfonyl fluoride (PFOS) and other chemicals since 1968. Employees were classified as follows: 1) by probability of exposure to PFASs; 2) by tertiles of PFOA serum concentrations. In a fraction (n = 120) of workers measurements of internal PFOA serum concentration were used to predict a cumulative serum PFOA concentration of each cohort member. Mortality rates were compared to that of the regional population using the standardized mortality ratio (SMR), and to that of the workers of a nearby metalworking factory in terms of risk ratio (RR), across categories of probability of PFASs exposure and tertiles of cumulative serum PFOA concentrations. Internal PFOA serum concentration among 120 workers in the 2000–2013 period was very high (Geometric Mean: 4048 ng/mL; range 19–91,900 ng/mL). The mortality of the chemical cohort was increased for liver cancer (SMR: 2.32; CI: 1.11–4.87), malignant neoplasm of lymphatic and haematopoietic tissue (SMR: 2.26; CI: 1.08–4.73). In the comparison with the cohort of workers from the metalworking factory, the RRs for mortality of the cohort were increased for overall mortality (RR: 1.42; CI: 1.12–1.79), diabetes (RR: 5.95; CI: 1.08–32.8), liver cancer (RR: 6.69; CI: 1.71–26.2) and liver cirrhosis (RR: 3.87; CI: 1.18–12.7). Mortality for these causes increased in association with probability of PFASs exposure and with tertiles of cumulative PFOA serum concentrations. The present is a small observational study with limited control over confounding factors. The cohort showed increased mortality for all causes and subjects in the highest cumulative internal dose of PFOA had a statistically significant increase for mortality of liver cancer, liver cirrhosis, diabetes, malignant neoplasms of lymphatic and haematopoietic tissue in both comparisons. Toxicological studies on PFOA and PFOS provide support for causality for the observed association with the risk for liver cirrhosis and liver cancer. •A broad spectrum of adverse health effects of PFASs.•Workers reported extremely high internal dose of PFOA.•An excess of mortality from liver cirrhosis and liver cancer among exposed workers.